The structure of PfGH50B, an agarase from the marine bacterium Pseudoalteromonas fuliginea PS47 - Pluvinage, Benjamin (Acta Crystallogr F Struct Biol Commun, 2020)
The recently identified marine bacterium Pseudoalteromonas fuliginea sp. PS47 possesses a polysaccharide-utilization locus dedicated to agarose degradation. In particular, it contains a gene (locus tag EU509_06755) encoding a β-agarase that belongs to glycoside hydrolase family 50 (GH50), PfGH50B. The 2.0 Å resolution X-ray crystal structure of PfGH50B reveals a rare complex multidomain fold that was found in two of the three previously determined GH50 structures. The structure comprises an N-terminal domain with a carbohydrate-binding module (CBM)-like fold fused to a C-terminal domain by a rigid linker. The CBM-like domain appears to function by extending the catalytic groove of the enzyme. Furthermore, the PfGH50B structure highlights key structural features in the mobile loops that may function to restrict the degree of polymerization of the neoagaro-oligosaccharide products and the enzyme processivity.